THE ANALYSIS OF GENERIC STRUCTURES AND COPY ELEMENTS IN ONLINE SHOP VIDEO ADVERTISEMENTS - Cut Ansi Faradhiba H., - (2018)
In this era of advance information and technology, many e-commerce platforms are rising and competing in creating certain strategies of advertising. Bukalapak, JD.ID, Lazada, Shopee, and Tokopedia as the most popular e-commerce platforms in Indonesia attract the customers by creating unique and out of the box video advertisements posted on YouTube. The objectives of this research are to investigate the realization of the generic structure elements in the video advertisements of the five mentioned online shops and to explore how copy elements are distributed in the generic structure of each video. This study is informed by Halliday and Hasan's (1989) theoretical model of genre analysis as the framework to see the generic structure of each video advertisement, and Maslen's (2009) perspective of copywriting to identify the copy elements contained in the generic structure. The data of video advertisements were mainly taken from each online shop's YouTube channel which were further transcribed and put into designed table. This study applies qualitative approach and employs simple descriptive statistical analysis for analyzing the generic structure of the video advertisements and the copy elements distribution. This study found that the generic structure of online shop video advertisements comprise five major generic elements, which are Opening, Background, Service Description, Persuasion, and Closing. The major copy elements that can be found in online shop video advertisements are Call to Action and Feature which are mainly placed in two of the generic elements, Persuasion and Closing. This study suggests that meanings are constructed intertextuality to result in intended meanings.